Unzipping supercontinent Pangea: Geologic, potential field data, and buried structures, and a case for sequential Atlantic opening - Aaron G. Stubblefield; Robert D. Hatcher; J. Wright Horton; David L. Daniels (Tectonophysics, 2023)

Comparison of hydrophobic and amphiphilic fractions of dissolved organic matter from a water reservoir by Fourier transform ion cyclotron resonance mass spectrometry - Guixue Song; Rajaa Mesfioui; Aaron Dotson; Paul Westerhoff; Patrick Hatcher (Journal of Soils and Sediments, 2018)

A comparative review of fisheries management experiences in the E uropean U nion and in other countries worldwide: I celand, A ustralia, and N ew Z ealand - Paul Marchal; Jesper Levring Andersen; Martin Aranda; Mike Fitzpatrick; Leyre Goti; Olivier Guyader; Gunnar Haraldsson; Aaron Hatcher; Troels Jacob Hegland; Pascal Le Floc'h; Claire Macher; Loretta Malvarosa; et al. (Fish and Fisheries, 2016)
This study compares the details and performance of fisheries management between the EU and a selection of other countries worldwide: Iceland, New Zealand, and Australia, which are considered in many respects to be among the most advanced in the world in fisheries management. Fisheries management in the EU , Iceland, Australia, and New Zealand has developed following different paths, despite being based on similar instruments and principles. Iceland, Australia, and New Zealand have been at the forefront of developing management practices such as stakeholder involvement, legally binding management targets (Australia, New Zealand), individual transferable quotas, and discard bans (Iceland, New Zealand). The EU has since the beginning of the 21st century taken significant steps to better involve stakeholders and establish quantitative targets through management plans, and a landing obligation is gradually being implemented from 2015 onward. The management of domestic fisheries resources in Australia, New Zealand, and Iceland has, overall, performed better than in the EU , in terms of conservation and economic efficiency. It should, however, be stressed that, compared to Australia, New Zealand, and Iceland, (i) initial over‐capacity was more of an issue in the EU when management measures became legally binding and also that (ii) EU has been progressive in developing common enforcement standards, on stocks shared by sovereign nations. The situation of EU fisheries has substantially improved over the period 2004–2013 in the northeast Atlantic, with fishery status getting close to that in the other jurisdictions, but the lack of recovery for Mediterranean fish stocks remains a concern.

Fisheries Buybacks - Aaron Hatcher (Fish and Fisheries, 2009)